2009
DOI: 10.1037/a0015676
|View full text |Cite
|
Sign up to set email alerts
|

Growth mixture modeling of academic achievement in children of varying birth weight risk.

Abstract: The extremes of birth weight and preterm birth are known to result in a host of adverse outcomes, yet studies to date largely have used cross-sectional designs and variable-centered methods to understand long-term sequelae. Growth mixture modeling (GMM) that utilizes an integrated person-and variablecentered approach was applied to identify latent classes of achievement from a cohort of school-age children born at varying birth weights. GMM analyses revealed 2 latent achievement classes for calculation, proble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
26
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 116 publications
3
26
0
Order By: Relevance
“…Espy, Fang, Charak, Minich and Taylor (2009) used growth mixture modeling to identify two distinct growth trajectories (growth clusters) for each academic domain: an average achievement trajectory and a persistently low achievement trajectory. In this study, 97 of the same participants underwent MRI in late adolescence.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Espy, Fang, Charak, Minich and Taylor (2009) used growth mixture modeling to identify two distinct growth trajectories (growth clusters) for each academic domain: an average achievement trajectory and a persistently low achievement trajectory. In this study, 97 of the same participants underwent MRI in late adolescence.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the technique is particularly relevant for examining groups of children with heterogeneous experiences and outcomes. In a sample of children with birth weights ranging from 440 to 4600g, Espy et al (2009) identified two growth trajectory clusters for the domains of mathematical calculation, applied problem solving, and reading respectively: 1) a typically-developing (average) cluster , characterized by average academic achievement across time, a faster rate of acceleration and an earlier peak in skill development; and 2) a poorly achieving (low) cluster , characterized by a persistent lag in performance across all study time points and a later peak in achievement growth. The probability of being classified into the low achieving clusters for mathematical calculation and problem solving increased as a function of decreasing birth weight, while increasing days of ventilation in the neonatal period were associated with an increased probability of low achievement in all three achievement domains.…”
mentioning
confidence: 99%
“…There are positive associations between fetal growth, early development and differentiation of the brain in the fetus, breastfeeding, and IQ, 38,39 and better results in various cognitive abilities and academic performance in the child. 34,[40][41][42] These effects depend on the nutritional intake of the mother, and folate has been suggested as 1 mediator of these positive effects on neural development. 43,44 However, the brain continues to develop through childhood and adolescence, [45][46][47][48] and the nutritional intake of the child himself/herself will be a major contributor to furthering brain maturation, 49 up to his/her individual potential for scholastic achievement, 50,51 although naturally conditioned by other background factors as well, such as genetic and SES factors.…”
Section: Figurementioning
confidence: 99%
“…Early identification is especially critical in view of evidence that learning problems frequently go unrecognized for several years after school entry (Avchen, Scott, & Mason, 2001). Determining a child’s need for special education at or soon after school entry, followed by appropriate interventions, has the potential to diminish long-term educational and social problems that occur in EPT/ELBW adolescents and young adults (Belsky & Mackinnon, 1994; Espy, Fang, Charak, Minich, & Taylor, 2009; Johnson et al, 2009; Rimm-Kaufmann et al, 2000). …”
Section: Introductionmentioning
confidence: 99%